Steven N. Kaplan (Journal of Finance, 2025)
Steve has made academic contributions to the study and understanding of private equity (PE), LBOs, venture capital (VC), corporate finance, corporate governance, and top executive talent.That work has also influenced industry/practitioners.Nineteen of his papers have accumulated more than 1,000 citations in Google Scholar including at least one in each of the five decades since the 1980s.Kaplan's work on PE began with his doctoral dissertation on LBOs.LBOs emerged